2001
DOI: 10.1164/ajrccm.164.4.2011004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Mitogen-activated Protein Kinases Differentially Regulate Eosinophil-activating Cytokine Release from Human Airway Smooth Muscle

Abstract: Airway smooth muscle (ASM) is a potential source of multiple proinflammatory cytokines during airway inflammation. In the present study, we examined a requirement for mitogen-activated protein (MAP) kinase activation for interleukin (IL)-1beta-stimulated GM-CSF, RANTES, and eotaxin release. IL-1beta induced concentration-dependent phosphorylation of p42/p44 extracellular signal-regulated kinases (ERKs), p38 MAP kinase, and c-Jun amino-terminal kinase (SAPK/JNK). p42/p44 ERK and p38 MAP kinase phosphorylation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
59
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 38 publications
12
59
2
1
Order By: Relevance
“…Similarly, the effect of SB-203580 on cytokine-induced mediator release has also been evaluated in human cultured ASMC. SB-203580 specifically inhibited cytokineinduced p38 kinase activity at concentrations up to 10 M and only partially inhibited JNK and ERK activity at 100 M (29). It is unlikely that inhibition of JNK activity contributed to the inhibitory action of SB-203580 on s-FKN release observed at the 20 M concentration used in this study.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Similarly, the effect of SB-203580 on cytokine-induced mediator release has also been evaluated in human cultured ASMC. SB-203580 specifically inhibited cytokineinduced p38 kinase activity at concentrations up to 10 M and only partially inhibited JNK and ERK activity at 100 M (29). It is unlikely that inhibition of JNK activity contributed to the inhibitory action of SB-203580 on s-FKN release observed at the 20 M concentration used in this study.…”
Section: Discussionmentioning
confidence: 61%
“…ASMC secretory responses of certain cytokines and chemokines are, in part, mediated by activation of the MAPK pathway (2,4,29,47). MAPK are a family of serine/threonine kinases, and at least three major groups that differ in their substrate specificity have been characterized: ERK, JNK, and p38 MAPK.…”
Section: Discussionmentioning
confidence: 99%
“…Davies et al (9) found that U-0126 reduced the in vitro kinase activity of p38␣ MAPK by ϳ25%. In contrast, studies in rat cardiomyocytes (45) and in human airway smooth muscle cells (17) have shown that U-0126 selectively inhibits p44/p42 MAPK activity without affecting p38 MAPK activity. To determine whether U-0126 inhibits the activity of p38 MAPK in response to insulin in adipocytes, we conducted an in vitro p38 MAPK assay.…”
Section: Impaired Phosphorylation Of P44/p42 Mapk By Pi3k Inhibitorsmentioning
confidence: 87%
“…The release of several cytokines, GM-CSF, regulated on activation normal T cells expressed and secreted (RANTES), and eotaxin, is dependent on the activation of the MAPKs in a complex fashion (9). Hallsworth et al (9) showed that GM-CSF release was dependent on the activation of p42/p44 but was suppressed by the activation of p38, and more recently Oltmanns et al (16) demonstrated the involvement of JNK in the TNF-␣-and IL-1␤-induced expression of GM-CSF, IL-8, and RANTES. These few examples demonstrate the complexity of cell responses to activation of the MAPKs.…”
Section: Discussionmentioning
confidence: 99%